Порівняльний аналіз методів аналізу ризиків Magerit та MEHARI - Хоменко, А. В. (ХНУРЭ, 2009)
Main deficiencies of risk analysis (RA) documentation were discussed. Methods Magerit and MEHARI were chosen as those are containing system features. Results of their comparison were given. A task of creating enhanced RA method suitable for practical appliance was posed.